Influence of Single Parenting on English Language Proficiency of Secondary School Students in Ekiti State, Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2025)
This study examines the influence of single parenting on secondary school students’ English Language proficiency in selected public secondary schools across Ekiti State, Nigeria. The study was guided by two objectives: to examine how single parenting influences students’ engagement with English Language learning, and to determine whether a significant difference exists in academic performance in English between students from single-parent and dual-parent households. A descriptive survey research design was adopted. The sample comprised 400 students selected using a multistage sampling technique: first, 20 public secondary schools were proportionately drawn across the 16 local government areas of Ekiti State to reflect both rural and urban settings. Subsequently, stratified random sampling was used to ensure balanced representation from single-parent and dual-parent families. Data collection involved a structured questionnaire assessing academic engagement and home support, alongside academic records in English Language over a three-year period. Descriptive statistics (frequency, percentage, mean) and inferential statistics (ANOVA) were employed to analyze the data. Results showed that students from dual-parent homes generally reported higher academic support, emotional encouragement, and access to English learning resources. Furthermore, repeated measures ANOVA revealed a statistically significant difference (p < 0.001) in English Language performance between the two groups across the three years, favoring students from dual-parent households. The findings underscore the role of family structure in shaping academic engagement and performance. The study recommends that schools, policymakers, and social support agencies collaborate to provide targeted academic and emotional support for students from single-parent homes to bridge the performance gap.